Ceratothoa oestroides Infection in European Sea Bass: Revealing a Long Misunderstood Relationship - Piazzon, M. Carla; Mladineo, Ivona; Dirks, Ron P.; Santidrián Yebra-Pimentel, Elena; Hrabar, Jerko; Sitjà-Bobadilla, Ariadna (Frontiers in Immunology, 2021)
Ceratothoa oestroides (Cymothoidea, Isopoda) is a generalist crustacean parasite that negatively affects the economic sustainability of European sea bass (Dicentrarchus labrax) aquaculture in the North-East Mediterranean. While mortalities are observed in fry and fingerlings, infection in juvenile and adult fish results in approximately 20% of growth retardation. A transcriptomic analysis (PCR array, RNA-Seq) was performed on organs (tongue, spleen, head kidney and liver) from infected vs. Ceratothoa-free sea bass fingerlings. Activation of local and systemic immune responses was detected, particularly in spleen, characterized by cytokines up-regulation (also in tongue), a general reshaping of the immunoglobulin response and suppression of T-cell mediated responses. Interestingly, starvation and iron transport and metabolism genes were strongly down-regulated, suggesting that the parasite feeding strategy is likely not hematophagous. Regulation of genes related to growth impairment and starvation supported the growth retardation observed in infected animals. Most differentially expressed transcripts were exclusive of a specific organ, however only in tongue the difference between infected and uninfected fish was significant. At the attachment/feeding site, the pathways involved in muscle contraction and intercellular junction were the most up-regulated, whereas pathways involved in fibrosis (extracellular matrix organization, collagen formation and biosynthesis) were down-regulated. These results suggest that the parasite-inflicted damage is successfully mitigated by the host, being characterized by regenerative processes that prevail over reparative ones.